Breaking barriers, changing paradigms: Africa's radical agenda for HIV sustainability - Chola, Mumbi; Robalo, Magda; Buse, Kent; Oduro-Bonsrah, Pokuaa; Ozoemene, Jekwu; Dieng, Abdoul; Akulu, Ruth; Madzima, Bernard; Coll-Seck, Awa Marie; Sheneberger, Robb; Nene, Sesupo Makakole; Sikazwe, Izukanji; et al. (Frontiers in Reproductive Health, 2025)
Despite significant progress in the HIV response, the sustainability of this journey is threatened by over-reliance on external support and imported and often inappropriate models. The recent sudden shifts in the United States Government's foreign aid policy have heightened the urgency for independence. Africa is at a critical point, which presents an opportunity to move from dependency on external assistance to establishing itself as a self-sustaining center of innovation and sustainable growth. Africa must reshape its approach to the HIV response by addressing the continent's over-reliance on external funding and shift towards self-sustainability and inclusiveness. For Africa to sustain its HIV response, it is critical to have African voices and leadership in the HIV response, adopt African-centric approaches in moving from silos to the integration of programme governance, ensure renewed governance and accountability frameworks, Africanizing research and development and also ensure African medicines security and sovereignty. Africa must leverage Ubuntu approaches to empowering communities, women, youth, and key and vulnerable populations, and work with community networks for service delivery. There must also be sustained HIV Programmes in Fragile and Post-conflict Settings. It is also critical to secure domestic financing through a continental approach to financing health and well-being. For Africa to realize the vision of a sustainable, African-led, and owned HIV response and health agenda, collective action is imperative. African stakeholders must fully support this agenda and claim it as their own in the spirit of Ubuntu, within the context of continental plans for transformation and revitalization. Together, we can realize the vision of the “Africa we want.”